A rare case of trisomy 18 with split-hand/split-foot malformation (SHFM) - Nydia Rena Benita Sihombing; Asri Purwanti; Agustini Utari (Faculty of Medicine, Diponegoro University, 2018)
Background: Trisomy 18 is one of the most prevalent chromosomal aberrations in newborns, with characteristic features of internal organs such as heart and kidney abnormalities, as well as craniofacial and musculoskeletal anomalies. We present a rare case of trisomy 18 with atypical features of split-hand/split-foot malformation (SHFM).Case Presentation: A four-months-old baby was brought to hospital with dyspnea and history of multiple congenital anomalies (MCA). Abnormalities found including brachycephaly, facial dysmorphisms, split hands and split feet. Other anomalies were atrial and ventricular septal defects, umbilical hernia, and right lung atelectasis. Based on physical examination and additional workups, SHFM was suspected. Genome-wide array analysis revealed gain on entire chromosome 18. Only few cases of trisomy 18 with SHFM have been reported, with split feet as the most findings. Conclusion: This case represents SHFM as a unique limb involvement in patient with trisomy 18, a valuable finding to be taken into account in trisomy 18 features. Careful examination and diagnosis as well as subsequent genetic counseling are granted, and routine cytogenetic analysis is vital as a first-tier diagnostic workup on patient with MCA.